FARMAKOGENETIK PENGOBATAN BETA 2 AGONIST DAN STEROID PADA PENDERITA ASMA - EM Sutrisna (Universitas Muhamadiyah Surakarta, 2014)
In the worldwide about 300 million people have asthma. β-2 agonists and steroids are widely prescribed drugs in the treatment of asthma. Different responses raises the suspicion of a genetic infiuence on the hosts response to the treatment of this disease. The purpose of this review is to provide a comprehensive understanding of the infiuence of genetic factors on the treatment of asthma. This review is done by the method in Pubmed search using keywords Pharmacogenetic asthma; polymorphism beta agonist AND asthma. The analysis shows that there are several genes that affect treatment response. ADRB2 gene affects the bronchodilatation response for asthmatics treated with β-2 agonist. CRHR1 gene polymorphism, Glucocorticoid-complex genes, and CER2 genes and TBX21 genes affect the response to corticosteroids inhalers.Keywords: Asthma, Pharmacogenetics, Treatment response